MARKET ANALYSIS OF PEARS IN ROMANIA - Elena SOARE; Irina-Adriana CHIURCIU; Aurelia-Vasilica BĂLAN; Livia DAVID (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the present paper there are highlighted several aspects referring to the activity of producing and marketing of pears in Romania during the period 2012-2017. In order to carry out a study that reflects the finalization of pears at national level, various specific indicators were analysed, such as: the total number of bearing pear trees in Romania; total pear production obtained internally; average pears production per tree at national level; the average price for table pears on the domestic market; imports and exports of pears both in terms of quantity and value. In Romania, nowadays, table pears are among the fruits appreciated by consumers, with an average annual consumption per capita of over 4.5 kg. In order to insure the amount of pears needed for domestic consumption, Romania imports significant annual quantities of pears. In this context, farmers in Romania can also focus on setting up pear plantations because they are less vulnerable to disease and are cost-effective even on less extensive surfaces. The National Institute of Statistics and specialized international sites were the main providers of statistical data that led to the realization of this study.